Phase III randomized study of the proposed adalimumab biosimilar GP2017 in psoriasis: impact of multiple switches. (15th July 2018) - Blauvelt, A.; Lacour, J.‐P.; Fowler, J.F.; Weinberg, J.M.; Gospodinov, D.; Schuck, E.; Jauch‐Lembach, J.; Balfour, A.; Leonardi, C.L.
Summary: Background: Adalimumab is used to treat several inflammatory diseases, including plaque psoriasis. GP2017 is a proposed adalimumab biosimilar. Objectives: To assess the impact of multiple switches between GP2017 and reference adalimumab (ref‐ADMB) following the demonstration of equivalent efficacy and similar safety and immunogenicity, in adult patients with active, clinically stable, moderate‐to‐severe plaque psoriasis. Methods: This 51‐week double‐blinded, phase III study randomly assigned patients to GP2017 ( n = 231) or ref‐ADMB ( n = 234) 80 mg subcutaneously at week 0, then 40 mg biweekly from week 1. At week 17, patients were rerandomized to switch ( n = 126) or continue ( n = 253) treatment. The primary end point was patients achieving ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) at week 16, with equivalence confirmed if the 95% confidence interval (CI) for the difference in PASI 75 between treatments was ± 18%. The key secondary end point was the change from baseline to week 16 in continuous PASI. Other end points were PASI over time; PASI 50, 75, 90 and100; pharmacokinetics; safety; tolerability and immunogenicity for the switched and continued treatment groups. Results: Equivalent efficacy between GP2017 and ref‐ADMB was confirmed for the primary (66·8% and 65·0%, respectively; 95% CI −7·46 to 11·15) and key secondary end points (−60·7% and −61·5%, respectively; 95% CI –3·15 to 4·84). PASI improved over time and was similar between treatment groups at week 16, and the switched and continued groups from weeks 17 to 51. There were no relevant safety or immunogenicity differences between GP2017 and ref‐ADMB at week 16, or the switched and continued groups from weeks 17 to 51. No hypersensitivity to adalimumab was reported upon switching. Conclusions: Following the demonstration of GP2017 biosimilarity to ref‐ADMB, switching up to four times between GP2017 and ref‐ADMB had no detectable impact on efficacy, safety or immunogenicity. Abstract : What's already known about this topic? Adalimumab is indicated for use in rheumatoid arthritis, psoriatic arthritis, plaque psoriasis, ankylosing spondylitis, juvenile idiopathic arthritis, hidradenitis suppurativa, Crohn disease, ulcerative colitis and uveitis. GP2017 is a proposed biosimilar to adalimumab. Previous analytical studies have shown that GP2017 and reference adalimumab have identical amino acid sequences, indistinguishable secondary and tertiary structures, the same level of post‐translational modifications and similar in vitro functionality. What does this study add? This phase III confirmatory efficacy and safety study demonstrated equivalent efficacy and similar safety of GP2017 and reference adalimumab in patients with moderate‐to‐severe plaque psoriasis. Additionally, switching up to four times between GP2017 and reference adalimumab had no impact on the incidence of adverse events or injection‐site reactions. The frequency of antidrug antibody development was similar between the switched and continued treatment groups, and there was no impact on efficacy. Linked Comment: Cline and Feldman. Br J Dermatol 2018;179 :557–558 . Respond to this article